Nutritional spoilage of tomato and brinjal fruits due to post-harvest fungi - Ghadsingh, P G; V, Mandge S (Current Botany, 2012)
In the present investigation spore suspension of previously isolated Alternaria solani, Colletotrichum sp., Fusarium solani, Phoma sp., Phomopsis vexans, Phytophthora sp., Phytophthora parasitica and Rhizopus stolonifer from tomato and brinjal were separately inoculated by sterilized disposable syringe in same aged tomato and brinjal fruits in aseptic condition. After seven days, biochemical parameters like change in dry weight, changes in protein content, changes in total sugar content and changes in vitamin C (Ascorbic acid) content from tomato and brinjal were estimated. Alternaria solani showed maximum decrease in dry weight of tomato fruit. Phytophthora parasitica showed maximum decrease in protein contents, total sugar contents and ascorbic acid contents of tomato fruit. Maximum decrease in dry weight contents of brinjal was due to Phomopsis vexans. Protein content of brinjal was found to be reduced due to all fungi, but Rhizopus stolonifer and Rhizoctonia solani showed maximum reduction in protein content of brinjal. Maximum decrease in total sugar content of tomato was observed due to Rhizopus stolonifer. Ascorbic acid content in brinjal was drastically decreased due to Rhizoctonia solani.